Osteochondroma of the distal tibia with associated varus deformity of ankle - Kapadiya, Shubham S.; Shah, Rushit M.; Patel, Nilkumar R.; Shah, Malkesh D.; Nayak , Hardik J. (International Journal of Research in Orthopaedics, 2024)
Osteochondroma or exostosis is a bony developmental anomaly, which arises from exophytic outgrowth on bone surfaces characteristically. The most common site is the distal femur followed by the proximal humerus and proximal tibia. It is made up of a bony protrusion that is covered by a cartilage cap. Osteochondroma is asymptomatic and grows away from the nearby joint. It is very common in kids and young adults. Sometimes patient comes in 2nd decade with complaints of pain and swelling. This paper reports a presentation of osteochondroma present over the right distal tibia.